Spin-polarized hydrogen and its isotopes: a rich class of quantum phases (Review Article) - Bešlić, I.; Vranješ Markić, L.; Boronat, J. (Физика низких температур, 2013)
We review the recent activity in the theoretical description of spin-polarized atomic hydrogen and its isotopes at very low temperatures. Spin-polarized hydrogen is the only system in nature that remains stable in the gas phase even in the zero temperature limit due to its small mass and weak interatomic interaction. Hydrogen and its heavier isotope tritium are bosons, the heavier mass of tritium producing a self-bound (liquid) system at zero temperature. The other isotope, deuterium, is a fermion with nuclear spin one making possible the study of three different quantum systems depending on the population of the three degenerate spin states. From the theoretical point of view, spin-polarized hydrogen is specially appealing because its interatomic potential is very accurately known making possible its precise quantum many-body study. The experimental study of atomic hydrogen has been very difficult due to its high recombination rate, but it finally led to its Bose–Einstein condensate state in 1998. Degeneracy has also been observed in thin films of hydrogen adsorbed on the ⁴He surface allowing for thepossibility of observing the Berezinskii–Kosterlitz–Thouless superfluid transition.